TRANSLATOR’S CREATIVITY IN RENDERING NEOLOGISMS OF A LITERARY TEXT - Wilczewski, Michał (Acta Neophilologica, 2011)
The article aims at analysing a concept of translator’s creativity and its function performed in the course of rendering neologism in a literary text. The linguistic material constitutes Michael Kandel’s translation of chosen robot names from the S-F novel Cyberiada by Stanisław Lem. The process of rendition is discussed from a literary and linguistic point of view. Therefore, such factors influencing translation as functions a particular name serves in the novel and its linguistic structure are taken into consideration. Moreover, motives for the employment of certain translation procedures, recommended by Peter Newmark, which pertain to neologisms are accounted for. The analysis shows that Kandel’s translation appears to be successful since, owing to his creativity, he menages to render such layers of neologism as its meaning, referent, form, connotation, function and, in some cases, sound. Doubtless, all these are not retained in each case due to obvious language impediments. Nevertheless, the neologisms sufficiently allow the TL reader to get to know futuristic characters of Cyberiada.